UNDERSTANDING BRAND STRATEGY: A REVIEW - Arundati, Rahajeng (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to understand more about brand strategy by reviewing several articles related to brand space, brand equity distribution, and digital brand strategy. Brand strategy is an important aspect for the success of companies that aim to differentiate themselves in a competitive market and increase company value. In today's marketplace, where success is increasingly challenging, a well-executed brand strategy is recognized as a strategic economic resource and source of competitive advantage. Brand space is an important concept in a company's brand strategy to manage brand extensions from time to time. There is a phenomenon known as brand equity dilution which is a challenge in formulating brand strategy. Brand equity dilution is a situation where the value and strength of a brand can be reduced due to various factors. On the other hand, as time goes by, traditional marketing methods are no longer effective, giving rise to the use of technology in implementing brand strategies. Digital brand strategy is a marketing activity that aims to build a brand and build meaningful relationships with customers. The existence of challenges in formulating brands and the lack of research that discusses branding strategies on social media makes it necessary to carry out this research. Considering that currently companies need to adapt in carrying out brand strategies that are no longer traditional marketing methods.